One Some Basic Problems of the Theory of Shakedown - Karczewski, J.; Konig, J.A. (Engineering Transactions, 1977)
The paper presents the observation that discrete structures of the global condition of shakedown does not need necessarily require that the shakedown condition of each element should be satisfied. A simple example illustrates the thesis. The practical importance of further research work on shake-down analysis of structures with unstable elements is emphasised.